Gst compliance time costs of smes in the northern region of malaysia - Mat Udin, Noraza; A.R., Rusniza; Mohd Suberi, Mardhiyah (2016)
The Malaysian government claims to always commit in making tax system more effective, efficient, comprehensive, transparent, fair and friendly. Thus, the indirect tax system had been reformed to implement the goods and services tax system (GST) since 1 April 2015. GST is meant to replace the former sales tax and services tax system which had been introduced since 1972 and 1975 respectively. Various issues ranging from difficulties in understanding GST application, increase in product price, confusion in GST procedures and cost associated with GST compliance have received debates among Malaysians. This paper reports the finding of a study conducted one year after the GST system implementation. It focuses on the compliance time cost i.e. the time spent by the small and medium enterprises (SMEs) in the northern region of Malaysia (Penang, Kedah, and Perlis) to comply with GST requirements. It is revealed that the time spent by taxpayers have increased in learning the new tax laws, record keeping, answering queries from tax authority, paying GST and claiming GST refund. In addition, the SMEs’ industries are varied in their opinions towards GST compliance time costs.